Comparison of serum zinc, calcium, and magnesium concentrations in women with pregnancy-induced hypertension and healthy pregnant women: A meta-analysis. (2nd April 2016) - He, Lianping; Lang, Lin; Li, Yijun; Liu, Qingqing; Yao, Yingshui
ABSTRACT: Objective : The relationship between serum zinc, magnesium, and calcium levels and pregnancy-induced hypertension (PIH) is controversial. The aim of our study was to determine whether or not serum zinc, magnesium, and calcium levels are associated with PIH. Methods : In our study, we searched databases, including Wangfang, Chinese National Knowledge Infrastructure, and PubMed, to find literature regarding the relationship between PIH and serum trace elements. Meta-analysis was performed using the Review Manager5.3 software. Results : A total of 14 articles were included in our study. The results of the meta-analysis indicated that patients with PIH had lower serum zinc (SMD = −1.14; 95% CI] = −1.69, −0.59; P < 0.05), calcium (MD = −0.26; 95% CI = −0.36, −0.15; P < 0.05), and magnesium concentration (MD = −0.0.06; 95% CI = −0.08, −0.05; P < 0.05) than healthy gravidas. Conclusion : Our research suggests that serum zinc, calcium, and magnesium concentrations may have an effect on PIH. Thus, the serum zinc, calcium, and magnesium levels could be measured for PIH patients.